Mathematical Communication Ability Viewed from Problem Solving Ability in Learning SAVI Model with Flash Media - Rini, Kurnia Setyo; Sugiarto, Sugiarto; Safa'atullah, Muhammad Fajar (Department of Mathematics, Universitas Negeri Semarang, 2017)
The aims of this research were (1) to test the mathematical communication ability of Junior High School 3 Salatiga in learning SAVI model with flash media achieved learning completeness classically, (2) to test the average of students’ mathematical communication ability in learning SAVI model with flash media compared with the average of students’ mathematical communication ability in learning DL model, and (3)to analyze the influences of learning SAVI model with flash media to group of students with low, medium, and high mathematical communication ability. The method used in this research is mixed method. Data analysis used included proportion test, averages difference test, and gain test. The results were (1) the mathematical communication ability of Junior High School 3 Salatiga in learning SAVI model with flash media achieved learning completeness classically, (2) the average of students’ mathematical communication ability in learning SAVI model with flash media higher than the average of students’ mathematical communication ability in learning DL model, and (3) learning SAVI model with flash media influenced to group of students with low, medium, and high mathematical communication ability.